Lives of the Prophets - Mohamad Reza Ghiasian
1 online resource.
Keywords: In Lives of the Prophets: The Illustrations to Hafiz-i Abru’s “Assembly of Chronicles” Mohamad Reza Ghiasian analyses two extant copies of the Majmaʿ al-tawarikh produced for the Timurid ruler Shahrukh (r. 1405–1447). The first manuscript is kept in Topkapı Palace and the second is widely dispersed. Codicological analysis of these manuscripts not only allows a better understanding of Hafiz-i Abru’s contributions to rewriting earlier history, but has served to identify the existence of a previously unrecognised copy of the Jamiʿ al-tawarikh produced at Rashid al-Din’s scriptorium. Through a meticulous close reading of both text and image, Mohamad Reza Ghiasian convincingly proves that numerous paintings of the dispersed manuscript were painted over the text before its dispersal in the early twentieth century.